Program Pelatihan dan Pendampingan Masyarakat di Desa Duda Timur Karangasem Bali - Putu Guntur Pramana Putra; Ni Made Mega Puspa Aristuti; Apriani Zebua; Bonefasia Satriani Budaya; Mario Redemtus Watu (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
This community training and mentoring program aims to improve participants' skills and knowledge in various fields, such as technical expertise, entrepreneurship and interpersonal skills. Participants will be involved in training and mentoring. This community training and mentoring program aims to encourage participants to make positive contributions to society through real action. Participants will be involved in projects designed to meet local community needs, such as environmental, educational or infrastructure development projects. Through this training and mentoring, participants are expected to be able to apply the skills and knowledge they gain during the training to have a real positive impact on society and build stronger relationships between communities. Activities during training programs and community service include: Gardening, harvesting snake fruit, cleaning areas around the houses of underprivileged residents, making canang for praying, looking for firewood, farming such as planting rice in rice fields, training tour guides to start a career in tourism and domestic violence seminars Tour guide training and domestic violence seminars provide opportunities for young people to continue their careers who will enter the world of tourism and can develop tourism in their villages. The Domestic Violence Seminar provides an understanding regarding harmony in the family for both family members and prospective new families.